Biotransformation of phosphorus in enhanced biological phosphorus removal sludge biochar - Qian, Tingting (2021)
Biochar derived from enhanced biological phosphorus removal (EBPR) sludge could be a potential phosphorus (P) fertilizer. Soil microorganisms play a regulating role on the turnover of P in soil. When the EBPR sludge biochar is added to soil, it would inevitably interact with soil microorganisms. Thus, for the wise use of the EBPR sludge biochar, it is imperative to understand the interaction between the biochar and soil microorganisms. In this study, Pseudomonas putida (P. putida), a common soil microorganism, was applied to investigate the biotransformation of P in two EBPR sludge biochars. The results reveal that P released from biochar produced at 700 °C (E700) was more easily absorbed by P. putida than that released from biochar produced at 400 °C (E400). This is attributed to the higher polyphosphates (poly-P) content in E700 and poly-P has higher affinity to P. putida surface compared to orthophosphates. Furthermore, E400 has a negative effect on intracellular poly-P formation in P. putida, which is probably caused by the oxidative stress induced by the free radicals from E400. As intracellular poly-P plays a critical role on bacteria survival and their interaction with surrounding environment, high-temperature biochar (E700) in this case would be more suitable for soil remediation.